Postsurgical Imaging of the Peroneal Tendons - Brodsky, James W.; Toppins, Anthony (Seminars in Musculoskeletal Radiology, 2012)
Peroneal tendon problems are most often related to two pathologies: dislocation or subluxation at the superior peroneal retinaculum and longitudinal split tears of the tendons themselves. The interpretation of postsurgical imaging is enhanced by understanding the surgical procedures performed to treat these. Imaging of the peroneal tendons is best done with combined anatomical and fluid-sensitive sequences, and it is especially improved by images done in a para-axial plane to accommodate the sharp curve in the tendons at the lateral malleolus. Use of a reduced field of view enhances spatial resolution.
Keywords: peroneal tendons; tendon tear; magnetic resonance imaging; postsurgical and/or postoperative; tendon subluxation; tendon reconstruction